2012
DOI: 10.5137/1019-5149.jtn.6651-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of acute interferon-beta 1b treatment after spinal cord injury

Abstract: AIm: The purpose of this trial was to investigate the effect of a well known immunomodulator -interferon beta-on traumatized spinal cord in terms of biochemical and histopathological features. mAterIAl and methOds: Twenty-four rats were used in this trial. The rats were divided into 3 groups. In the first group of rats, spinal cord injury was created by the weight drop method and interferon beta was administered. In the second group, physiological saline was administered. Third group was used as control. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Sengul et al reported that histopathological evaluation in the physiological saline group showed a considerable increase in hemorrhage, edema, neuronal degeneration, and inflammation in a spinal cord injury model (36). In the present study, considerable laceration, diffuse hemorrhage, intense edema, and neuronal degeneration (Nissl losses and red degeneration) were observed in the gray matter and edema, intense axonal degeneration, and spherule structures were observed in the white matter in the sham group (Figure 3B).…”
Section: A B C Dsupporting
confidence: 62%
See 1 more Smart Citation
“…Sengul et al reported that histopathological evaluation in the physiological saline group showed a considerable increase in hemorrhage, edema, neuronal degeneration, and inflammation in a spinal cord injury model (36). In the present study, considerable laceration, diffuse hemorrhage, intense edema, and neuronal degeneration (Nissl losses and red degeneration) were observed in the gray matter and edema, intense axonal degeneration, and spherule structures were observed in the white matter in the sham group (Figure 3B).…”
Section: A B C Dsupporting
confidence: 62%
“…against spinal cord injuries are aimed at preventing secondary injuries (36). Contusion models are important tools for exploring progressive secondary tissue injury, demyelination, and apoptosis in spinal cord injury (40).…”
Section: A B C Dmentioning
confidence: 99%
“…With respect to other therapies involving chaperones, improvement in functional recovery in rats with a contusion spinal cord injury following interferon-beta 1b treatment was found to be related to enhanced HSP70 expression in the cord along with reduced polymorphonuclear leucocyte infiltration, hemorrhage, oedema and necrosis (Sengul et al, 2013 ). An interesting therapeutic intervention in spinal cord injury experiments has been the use of exercise in injured animals.…”
Section: Therapeutic Strategies That Involve Chaperonesmentioning
confidence: 99%
“…SKY, lokal ve sistemik sekonder mekanizmaları tetikleyerek, esas olarak yaygın hücre ölümünden sorumlu olan kronik bir inflamatuar duruma neden olur [15]. Omurilik yaralanmalarında birincil yaralanmayı önlemenin imkânsız olmasından dolayı araştırmacıların geliştirmeye çalıştığı tedavi stratejileri ikincil yaralanmaları önlemeyi amaçlamaktadır [16]. Erken evrede, klinikte omurilik yaralanmasının geleneksel tedavisi, yüksek dozlarda metilprednizolon (MP) ile kombine cerrahi tedavidir [17].…”
Section: Discussionunclassified